INTRODUCING AND TEACHING “TUNJUK AJAR MELAYU”AS A CORRUPTION PREVENTION STRATEGY - Nurfaizal Nurfaizal (Asia Pacific Fraud Journal, 2018)
Corruption has damaged the life of nation and state. The government has established an agency called Corruption Eradication Commission (KPK). Various efforts have been made by KPK, in order to eradicate and prevent corruption. The efforts that can be filed to prevent corruption are by raising and socializing the noble values of local wisdom. In Riau, this noble value is known as “Tunjuk Ajar Melayu” (TAM). TAM is an oral literature of Malay, inherited from generation to generation as poetry, poem, gurindam, proverb, seloka, fairy tale, legend or folklore which contain the teaching of virtue for the sake of the value of human dignity and glory. The oral literature was recorded by Tenas Effendy, entitled «Tunjuk Ajar Melayu». In the book, it is mentioned the so called Malay principle «Sifat Dua Puluh Lima». These values are reinforced by the twenty-five «Pantangan anak Melayu». In one hand, the socialization of TAM can be done through formal education such as schools from primary level to university, government and private agencies. On the other hand, the non formal way as courses, training and upgrading would be helpful to reach the whole community. At the end, indicating and teaching TAM is expected to make the noble values of local wisdom come through into the hearts of Malay youth and to the people of Bumi Lancang Kuning, therefore the corruption will be prevented effectively, since it is considered as taboo and prohibition of Malay youth.